HAMBATAN DALAM PENERAPAN METODE TAHFIDZ DI SDTQ NURUN NABI - Muhammad Sya’ban Astsani (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2026)
The low motivation among some students to memorize the Quran at SDTQ Nurun Nabi in Banda Aceh certainly did not arise without cause; rather, there are factors influencing it, one of which is a memorization method that can make students feel bored and sleepy. Therefore, this study offers a solution by employing a storytelling method for students in memorizing the Quran at SDTQ Nurun Nabi Banda Aceh. This research adopts a qualitative approach and is of a descriptive nature. The research subjects consist of the principal of SDTQ Banda Aceh, Quran memorization teachers, and students. Data collection techniques included observation, interviews, and documentation. Based on the research results, it can be concluded that: the application of the storytelling method in memorizing the Quran at SDTQ Nurun Nabi Banda Aceh is carried out through the presentation of Quranic stories prepared by the teachers to facilitate students in memorizing the Quran. Teachers first prepare the stories and visual aids that can assist them in presenting the prepared stories to facilitate the Quran memorization process, which takes place over two days: Tuesday and Friday. The impact of the storytelling method on students’ motivation to memorize the Qur’an at SDTQ Nurun Nabi in Banda Aceh is an increase in motivation to retain the Qur’anic memorization; students are motivated to expand their Qur’anic memorization, and they read stories about Islamic figures while memorizing the Qur’an. The challenges faced by teachers in applying the storytelling method to enhance students’ motivation to memorize the Qur’an at SDTQ Nurun Nabi Banda Aceh include laziness among those memorizing the Qur’an, poor time management, and the use of recitation recordings as a memorization aid.